2018
DOI: 10.1007/s10393-017-1307-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Efficacy of Landsat-Derived Environmental Covariates for Predicting Malaria Distribution in Rural Villages of Vhembe District, South Africa

Abstract: Malaria in South Africa is still a problem despite existing efforts to eradicate the disease. In the Vhembe District Municipality, malaria prevalence is still high, with a mean incidence rate of 328.2 per 100,0000 persons/year. This study aimed at evaluating environmental covariates, such as vegetation moisture and vegetation greenness, associated with malaria vector distribution for better predictability towards rapid and efficient disease management and control. The 2005 malaria incidence data combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 65 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…arabiensis) population dynamics on malaria transmission was investigated over 26,28,40,43], Limpopo [28] and Mpumalanga provinces [11]. Other studies also confirm that the vector population correlates with the resurgence [5,42,44]. More importantly, the resurgence has been traced to the arrival of new mosquito species across the epidemic regions [18,45].…”
Section: Epidemiological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…arabiensis) population dynamics on malaria transmission was investigated over 26,28,40,43], Limpopo [28] and Mpumalanga provinces [11]. Other studies also confirm that the vector population correlates with the resurgence [5,42,44]. More importantly, the resurgence has been traced to the arrival of new mosquito species across the epidemic regions [18,45].…”
Section: Epidemiological Factorsmentioning
confidence: 99%
“…A high correlation was reported between malaria cases and derived environmental metrics such as the Normalized Difference Water Index (NDVI) [5,31] Normalized Difference Water Index (NDWI) and altitude, water body and irrigated land [5,60] in Mpumalanga province. Furthermore, Malahlela [42] concluded that malaria resurgence in Limpopo province is traceable to vegetation moisture and vegetation greenness, which are proxy/surrogate for rainfall. The availability of an adequate amount of rainfall for the provision of ideal environmental conditions (such as open water, green vegetation) provides suitable breeding and resting places for the major vector.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Limpopo [24] and Mpumalanga provinces [8]. With statistical approach, other studies confirm mosquitos' impact on the resurgence [5,38,40]. More importantly, the resurgence has been traced to arrival of new mosquito species across the epidemic regions [15].…”
Section: Epidemiological Factorsmentioning
confidence: 96%
“…Half of the 24 papers highlight the importance of mosquito abundance on malaria resurgence across the epidemic regions in South Africa [5,8,15,21,[22][23][24][36][37][38][39][40]. For example, using climate-based mathematical models, the impact of mosquito (mainly An.…”
Section: Epidemiological Factorsmentioning
confidence: 99%
See 1 more Smart Citation